DETEKSI VIRUS TUNGRO PADA PADI DI BENGKULU - Mimi Sutrawati; Yenny Sariasih; Priyatiningsih Priyatiningsih; Fausiah T. Ladja (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2019)
[DETECTION OF TUNGRO VIRUS ON RICE IN BENGKULU]. Several types of viruses have been reported to infect rice plants in Indonesia, including tungro, dwarf grass, and empty dwarfs. The spread of tungro in Indonesia in the beginning was only limited to certain regions in South Sulawesi, South Kalimantan, West Nusa Tenggara and North Sulawesi, but later it expanded to East Java, Central Java and Yogyakarta. In this study a tungro disease survey was conducted in several areas in Bengkulu Province. Virus detection is done by Loop-medated isothermal amplification (LAMP). Observations in the field showed that there were typical symptoms of tungro infection in rice plants, namely orange leaves starting from leaves to 2 and 3, little tillers, stunted plant growth. The results of detection with LampPCR showed rice samples from the district Pondok Kelapa Kab Bengkulu Tengah is positively infected with tungro virus.